Spatio-temporal variables of the circle on a pommel horse as a function of level of practice - Baudry, L.; Leroy, D.; Chollet, D. (Expertise in Elite sport. 2nd International Days of Sport Sciences, 12.-15. November 2002, INSEP, Paris (France), 2002)
Introduction